Hypoxia-inducible factor-1α signaling in cardiac adaptations to hypobaric hypoxia - Johnson, Anna C., author (Colorado State University. Libraries, 2024)
Previous data from the Chicco lab demonstrated that skeletal muscle metabolic adaptations to hypobaric hypoxia (HH) involves glucocorticoid receptor (GR) signaling, but not hypoxia inducible factor (HIF)-1α. The present study investigated whether the same is true in cardiac muscle. Male F344 rats were given a glucocorticoid receptor blocker (RU486) or no drug beginning five days before and throughout a fifteen-day exposure to 17,200 feet simulated in a hypobaric chamber or remained at Fort Collins elevation at 5,003 feet. Cardiac tissue was collected and analyzed for expression of GR, HIF1-α, VLCAD (a fatty acid oxidation enzyme), and each of the five complexes involved in (OXPHOS) oxidative phosphorylation. Current data indicates that while HH had no effect on cardiac GR expression, HIF1-α protein levels were elevated in the right ventricle (RV) and left ventricle (LV). Consistent with this finding, VLCAD expression was lower in the RV, with no effect of RU486 treatment, while the opposite trend was previously seen in skeletal muscle. Taken together, our results thus far indicate that in contrast to skeletal muscle, HIF1-α, rather than GR signaling, may play an important role in cardiac responses to HH.
Department of Biomedical Sciences, Cardiovascular Research Center, Colorado State University.
Keywords: HIF-1α; hypoxia; glucocorticoid receptor; cardiomyocytes; high-altitude